Are Personality Traits in Harry Potter Novels Gender-Based? The Case of Harry, Ron and Hermione - Sultan, Shrouk; Saleh, Basma; ElSherbini, Asmaa (International Journal of Language and Literary Studies, 2022)
Humans display several different attitudes towards others and towards the life situations and challenges they encounter. Gender is said to be a factor that can determine one’s likeability to show a certain attitude rather than another. Traditionally speaking, men are expected to act one way towards something, while women are expected to act in a different way towards the same thing. This paper aims to identify the extent to which the Harry Potter series abides by, or challenges, the traditional gender stereotypes of human attitudes and reactions. Thus, this paper should help to decide if the three main characters in Harry Potter: Harry, Ron and Hermione, are depicted, in terms of their personality traits, on the basis of traditional gender norms. On a wider scope, the paper aims to investigate the role that widely-read fiction, such as Harry Potter, plays to reinforce traditional ideas or to encourage more liberating views. To achieve these aims, the attitudes and reactions of the three major characters of the novels are to be analyzed. Two of these characters are male: Harry and Ron, while the third: Hermione, is female. The attitudes and reactions of these three characters are to be measured according to how much they take risks or follow the rules, how much they are caring and nurturing, rude, and persistent.